Pengembangan LKPD Problem Based Learning Berbantuan Media Vascak untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa pada Materi Kalor dan Perpindahannya: Indonesia - Nala Munirotus Sylfi; Dinar Maftukh Fajar (Universitas Garut, 2026)
This study aimed to develop a Problem-Based Learning (PBL)-based Student Worksheet (LKPD) integrated with Vascak simulation media to improve students' problem-solving skills on the topic of heat and heat transfer. The study employed the Research and Development (R&D) method based on the 4-D development model, consisting of the define, design, develop, and disseminate stages. The participants included subject-matter experts, media experts, practitioner experts, and seventh-grade students of SMPN 1 Srono. Data were collected using validation sheets, practicality questionnaires, and problem-solving skill tests. The developed LKPD achieved a validity score of 91.89%, indicating that it was highly valid. The large-scale practicality assessment reached 83.75%, showing that the LKPD was highly practical for classroom implementation. Moreover, the effectiveness test produced an N-Gain score of 0.61 (moderate category), reflecting improved students' problem-solving skills after using the developed LKPD. These findings indicate that the PBL-based LKPD integrated with Vascak simulation media is effective in enhancing students' problem-solving skills. The novelty of this study lies in integrating the LKPD, the PBL model, and Vascak simulation media into a systematically developed instructional resource for science learning.Keywords: Heat, problem-based learning, problem-solving ability, student worksheets, Vascak media